A first econometric analysis of the CRIX family - Shi Chen; Cathy Yi-Hsuan Chen; Wolfgang Karl Härdle; TM Lee; Bobby Ong (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
The CRIX (CRyptocurrency IndeX) has been constructed based on approximately 30 cryptos and captures high coverage of available market capitalisation. The CRIX index family covers a range of cryptos based on di erent liquidity rules and various model selection criteria. Details of ECRIX (Exact CRIX), EFCRIX (Exact Full CRIX) and also intraday CRIX movements may be found on the webpage of hu.berlin/crix.
Keywords: 330; Index construction; CRIX; information criteria; model selection; AIC; BIC; market analysis; bitcoin; cryptocurrency